Efektivitas Abdominal Massage dalam Mengatasi Konstipasi pada Lansia: Review - wantonoro (Universitas Muhammadiyah Klaten, 2025)
The aging process and chronic diseases can increase the risk of constipation in the elderly. Abdominal massage is known to affect brain function through the gut-brain axis, thereby enhancing intestinal motility, stimulating intestinal peristalsis, and improving bowel frequency while reducing difficulty during defecation. Although abdominal massage has been reported to be effective, further research is still needed specifically for the elderly population. This review aims to evaluate the implementation of abdominal massage in managing constipation among the elderly based on Randomized Controlled Trial (RCT) studies. The search results yielded 145 related journals, and after selection, six articles met the inclusion criteria, which were: 1) studies with abdominal massage intervention, 2) respondents in the elderly category, 3) RCT studies, and 4) full-text articles in English published between 2020-2025. Abdominal massage is recommended as a non-pharmacological therapy alternative for managing constipation in the elderly. Training to enhance the abilities of nurses and caregivers in performing abdominal massage is crucial for non-pharmacological constipation management. Further studies on specific methods or techniques of abdominal massage for the elderly are recommended to improve the effectiveness of this therapy